Crime Fiction of Dana Stabenow and Linda Barnes - Čermáková, Denisa (Univerzita Pardubice, 2024)
This diploma thesis deals with the crime fiction and with the private eye in American crime literature. Theoretical part describes crime fiction, basic terminology and authors and examples of their works. Practical part describes main characters of the books, their investigative methods, and places where the books are set.
Keywords: soukromé očko; americká drsná škola; detektivní fikce; kriminální fikce; Stabenow, Dana; Barnes, Linda; private eye; American hard-boiled school; detective fiction; crime fiction